PERANAN VEGETASI TERHADAP KEHADIRAN KUPU-KUPU Graphium androcles Boisduval (LEPIDOPTERA:PAPILIONIDAE) DI SEKITAR AREAL WISATA PATTUNUANG DAN BANTIMURUNG, TAMAN NASIONAL BANTIMURUNG BULUSARAUNG, SULAWESI SELATAN - Harlina, Harlina (Pro-Life, 2016)
Research on the use of plants by Graphium androclesbutterfly around of the travelarea Bantimurung andPattunuang was in April 2014 to March 2015. The method of observation using vegetation analysis. Method of observation and interviews do with the inventory type of host plants, food plants and shelter. The results showed that the number of individuals G. androcles, namely 61 individu, which consisted of 45 individu found in travel areas Pattunuang and 16 individu found in the travelarea Bantimurung. was found 5 nectar plant species, one species of host plants, and 7 species as shelter. G.androcles female butterflies lay their eggs on the leaves Uvaria rufa from Family Annonaceae that encountered around travel areaPattunuang, but not found in Bantimurung. Plants mature trees that dominate the area, namely travel area Pattunuang Arenga pinnata (INP 17,15) and Canangium odoratum with INP 17,02. In the travel area Bantimurung dominated by Ficus sp (INP 29,69), followed by Macaranga sp (INP 28,02). The tree has a height of 7-10 m from the ground. G. androclesbutterflies oftenitsused as a place of rest, play, orshelter.